(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
Hypertrophic gingivitis is a periodontal condition characterized by excessive enlargement of gingival tissues caused by inflammatory and proliferative processes. The disease may significantly affect oral hygiene, aesthetics, and overall periodontal health. Effective treatment requires elimination of etiological factors and restoration of normal gingival morphology. The aim of this study was to evaluate modern treatment approaches for hypertrophic gingivitis based on contemporary scientific literature. A review of clinical studies and periodontal research published between 2000 and 2025 was conducted. The analysis demonstrated that treatment methods include professional oral hygiene procedures, anti-inflammatory therapy, medication management, and surgical correction in severe cases. Conservative treatment is effective in early stages, while advanced fibrous forms often require gingivectomy or other surgical procedures. Comprehensive periodontal therapy combined with patient education significantly improves treatment outcomes and prevents disease recurrence.